623 Gastroschisis Transfers Conducted by the West Midlands Neonatal Transfer Service. (October 2012) - Shenvi, A; Harrison, J; Philpott, A; Dhillon, A; Rasiah, SV
Abstract : Background and Aims: Gastroschisis has an incidence of approx. 3 per 10, 000 1 with an increasing trend in the UK. 2 Gastroschisis requires immediate postnatal surgical care. Within the West Midlands, newborns with gastroschisis are resuscitated and transferred by WMNTS to a surgical centre. Network guidelines suggest completion of transfers within 4 hours of birth. Methods: Retrospective review of gastroschisis transfers conducted by the WMNTS from Jan 2008 to Dec 2011. Results: Conclusions: 88 transfers for gastroschisis were conducted over the period. 91% babies were kept within region and transferred within an average time of 80 min in keeping with the network guideline. There have been no patient related clinical incidents. References: Surgical Clinics of North America - Volume 86, Issue 2 (April 2006). Kilby MD BMJ 2006; 332:250 doi: 10.1136/bmj.332.7536.250.